The Pentateuch : Introducing the Torah - Dozeman, Thomas B. (Introducing Israel's scriptures., 2017)
The Pentateuch is the heart of the Hebrew Bible and the foundational document of Judaism. It is also the focus of tremendous scholarly exploration and debate today regarding the complex history of its composition. This history will be explored along with analysis of the historical background and ancient Near Eastern parallels for its primeval history, its ancestry narratives, and laws, the theological purposes of its final redaction, and the diverse ways it is interpreted in communities today. In this textbook, Thomas B. Dozeman, one of the leading scholars of the Pentateuch today, introduces students to its contents and structure of each book, and orients them to the Pentateuch's place in the Hebrew Bible and in the interpretive traditions of Judaism and Christianity. Dozeman deftly introduces the key interpretive questions and methods that shape contemporary scholarship and explains their consequences, inviting students into the invigorating work of interpretation today.